Endogenous Antigen Presentation of MHC Class II Epitopes through Non-Autophagic Pathways - Leung, Carol S. K. (Frontiers in Immunology, 2015)
Antigenic peptides presented by major histocompatibility complex (MHC) class II molecules are generally derived from exogenous proteins acquired by antigen presenting cells. However, in some circumstances, MHC class II molecules can present intracellular proteins expressed within the antigen-presenting cells. There are several described pathways by which endogenous antigens are degraded and gain access to MHC class II molecules. These include autophagy and other non-autophagic pathways; the latter category includes the MHC class I-like pathways, heat shock protein 90-mediated pathways, and internalization from the plasma membrane. This review will summarize and discuss the non-autophagic pathways.